(3GdfXQjI GdYGeI ddGKHGJ aj GdehGO GdeOfjI h GdJLGQjI (B/s - (3Sdje, YUGe GfhQs ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2010)
(3GdGKHGJ GdbVGFj h CgejJg h GdeUGOQ GdQSejI dbhGYOg , JaGhJ GdeHGOF GdegjefI Ydi bhGYO GdGKHGJ aj GdbGfhf GdebGQf , eMd GdGKHGJ h YHDg , GdcJGHI (B: (3GdeMQQGJ GdQSejI h GdeMQQGJ GdYQajI , WQb GdGKHGJ PGJ GdbhI GdeMOhOI , GdWQb GdeYajI ef GdGKHGJ (B: (3GdGbQGQG , Gdjejf , MLjI GdGeQ GdebVi (B.s
Keywords: (3EbGeI GdYOds; (3GdbGfhfs; (3GdbVGAs